2018
DOI: 10.2146/ajhp170262
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized, citywide process for managing smart-pump drug libraries

Abstract: Through implementation of a standardized, consensus-driven process for smart-pump drug library optimization, ICPS member health systems reduced clinically insignificant smart-pump alerts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…This may indicate that adjustment of the dosing limits in the drug library could significantly decrease alert burden while continuing to promote patient safety by alerting for more significant overdoses. Several authors have demonstrated the utility of small dosing limit adjustments to decrease the number of nonactionable alerts, but more evidence is needed to understand the effect of changing dosing limits on patient safety [13, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that adjustment of the dosing limits in the drug library could significantly decrease alert burden while continuing to promote patient safety by alerting for more significant overdoses. Several authors have demonstrated the utility of small dosing limit adjustments to decrease the number of nonactionable alerts, but more evidence is needed to understand the effect of changing dosing limits on patient safety [13, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated the utility of small dosing limit adjustments to decrease the number of nonactionable alerts, but more evidence is needed to understand the effect of changing dosing limits on patient safety. [13,28,29] Others have shown that alert number differs by time of day, day of the week, and month. [15] We found that overall alert number is highest on the evening shift but we contribute this to the fact that the majority of new fluids, TPN and lipids are hung during this shift.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated the utility of small dosing limit adjustments to decrease the number of nonactionable alerts, but more evidence is needed to understand the effect of changing dosing limits on patient safety. [13,26,27] Others have shown that alert number differs by time of day, day of the week, and month. [15] We found that overall alert number is highest on the evening shift but we contribute this to the fact that the majority of new fluids, TPN and lipids are hung during this shift.…”
Section: Discussionmentioning
confidence: 99%